Earnings Management within Multinational Corporations - Beuselinck, Christof; Cascino, Stefano; Deloof, Marc; Vanstraelen, Ann (The Accounting Review, 2019)
ABSTRACT Using a large sample of multinational corporations (MNCs), we examine the location of earnings management within the firm. We posit and find that MNCs manage their consolidated earnings through an orchestrated reporting strategy across subsidiaries over which they exert significant influence. Specifically, we find that headquarters' influence on subsidiary earnings management increases with the degree of subsidiary integration and the extent of earnings management opportunities. Most importantly, we provide evidence that MNCs exploit regulatory arbitrage opportunities arising from cross-country differences in institutional quality. We document that, in response to exogenous improvements in the quality of their home-country institutions, MNCs rebalance their reporting strategies by clustering earnings management in subsidiaries from countries with more lenient regulations. Taken together, our findings yield important insights on the drivers of earnings management location within the firm and highlight the need for better cross-country coordination in regulatory design. JEL Classifications: F23; G15; G34; G38; M41; M48.